(untitled) (Journal of the College of Basic Education, 2022)
The research seeks to identify the most important values ​​involved in social marketing, targeting the individuals of the holy city of Karbala, and their relationship to social change.The results of the research showed that the various values ​​of social solidarity ranked first with 33% of the total percentages of the values ​​researched, while the religious, cultural and educational values ​​occupied the last rank with 9%, due to the lack of interest in the study sample. Religious events and the resulting environmental damage extend for long periods, some of which may reach months.